2007
DOI: 10.1038/sj.pcan.4500980
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in young men after radical prostatectomy

Abstract: Urinary and sexual function and bother are important outcomes following radical prostatectomy (RP). Since urinary and sexual function are age-related, post-operative bother may vary by age. This study explores the disease-specific quality-of-life outcomes in young men compared with older men undergoing RP. Using CaPSURE data, we identified men who underwent RP and completed the UCLA Prostate Cancer Index (PCI) before and 1-year post-RP. Men were stratified by age (o55 years, 55-64, X65). Multivariate regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
3
16
0
1
Order By: Relevance
“…Those who took PDE-5 inhibitors may have been more motivated to maintain their baseline sexual function. This is consistent with other reports in which baseline sexual function and the use of sexual aids correlated with worsening sexual concern after RP [77]. Conversely, Japanese men who did not take PDE-5 inhibitors may have viewed ED as a natural part of aging and a normal side effect of cancer treatment.…”
Section: The Effect Of Sexual Qol On Pde-5 Inhibitors After Radical Psupporting
confidence: 82%
“…Those who took PDE-5 inhibitors may have been more motivated to maintain their baseline sexual function. This is consistent with other reports in which baseline sexual function and the use of sexual aids correlated with worsening sexual concern after RP [77]. Conversely, Japanese men who did not take PDE-5 inhibitors may have viewed ED as a natural part of aging and a normal side effect of cancer treatment.…”
Section: The Effect Of Sexual Qol On Pde-5 Inhibitors After Radical Psupporting
confidence: 82%
“…4 Moreover, several authors have reported that the return of serum testosterone level (T) to normal range during intermittent androgen deprivation is associated with a significant improvement of general well-being, and urinary (UF) and sexual function (SF). [5][6][7] In particular, QOL benefits in the off-treatment phase are shown by a shift toward baseline levels in the scales depicting physical and work functions, urgency, nocturia, impotence and sexual performance.…”
Section: Introductionmentioning
confidence: 99%
“…3,[7][8][9] Many patients continue to experience symptoms 1-2 years later. 1,3,4,6,7,10,11 Pain, fatigue, and physical and social function are also affected. 1,3,7,8,10 Most studies measured quality of life using psychometric instruments.…”
Section: Introductionmentioning
confidence: 99%